ANALISIS TINGKAT KEPUASAN KONSUMEN TERHADAP PELAYANAN DABU – DABU LEMONG BOULEVARD KARANGRIA - Herlina Anggie Tangkere; Joachim Noch Karel Dumais; Tommy Fredy Lolowang (AGRI-SOSIOEKONOMI, 2020)
The purpose of this study was to analyze the level of customer satisfaction with the services provided by the "Dabu-Dabu Lemong" restaurant. This research was conducted from December to February 2020. The data used in this study are primary data and secondary data. The sampling method in this study uses accidental sampling. Primary Data is data obtained through interviews and direct observations or observations. Interviews were conducted with management and customers. Questionnaires were distributed to customers as respondents. Secondary Data is the collection of data from other parties in the form of data obtained from various sources of linear study including books, internet, journals, and the results of previous research. Analysis of the data used is descriptive data analysis using a Likert scale. The results showed that the overall level of customer satisfaction with service at "Dabu-dabu Lemong" Boulevard Boulevard Karangria classified as very satisfied with the consumer satisfaction index figure of 80.9%.*eprm*